Carbon dioxide capture by metal organic frameworks - Saha, Subhadeep; Chandra, Suman; Garai, Bikash; Banerjee, Rahul (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2012)
The design and synthesis of functionalized metal organic framework materials (MOFs) for reversible physisorption of CO2 is discussed. This strategy of CO2 adsorption in MOFs requires less energy for regeneration than materials relying on chemisorption. As a result the MOFs have received considerable attention as sorbent materials for strategic gases such as CO2 and H,. In this review, we have discussed different MOFs and hybrid materials containing MOFs which can adsorb CO2 at room temperature. In order to achieve high adsorption capacity, fast CO2 adsorption-desorption and low energy requirement for regeneration are necessary. Several avenues for increasing the CO2 adsorption capacity of such materials, for instance, introduction of open metal sites and the use of ligand molecules with specific functionalities (like -OH or -NH2) have been described. It has been observed that CO2 loading capacity of MOFs increases with functionalization. Herein, we have discussed how N-containing and fluorinated MOFs are designed to achieve higher CO2 loading than their non-functionalized counterparts. Nanocarbons (e.g. carbon nanotubes, carbon nanofibres, etc.) are porous materials and a blend of these porous materials with porous MOFs or porous carbon derived from MOFs may act as a better adsorbate than even the pure materials. Enhancement of CO2 loading by nanocarbon-MOF hybrid material is also discussed.
Keywords: Carbon dioxide adsorbents; Carbon dioxide capture; hybrid materials; Metal organic frameworks; Nanocarbons; Porous nanocarbons

Chemically stable multilayered covalent organic nanosheets from covalent organic frameworks via mechanical delamination - Chandra, Suman; Kandambeth, Sharath; Biswal, Bishnu P.; Lukose, Binit; Kunjir, Shrikant M.; Chaudhary, Minakshi V.; BabaRao, Ravichandar; Heine, Thomas; Banerjee, Rahul (Journal of the American Chemical Society, 2013)
A series of five thermally and chemically stable functionalized covalent organic frameworks (COFs), namely, TpPa-NO2, TpPa-F-4, TpBD-(NO2)(2), TpBD-Me-2, and TpBD-(OMe)(2) were synthesized by employing the solvothermal aldehyde-amine Schiff base condensation reaction. In order to complete the series, previously reported TpPa-1, TpPa-2, and TpBD have also been synthesized, and altogether, eight COFs were fully characterized through powder X-ray diffraction (PXRD), Fourier transform IR (FT-IR) spectroscopy, C-13 solid-state NMR spectroscopy, and thermogravimetric analysis. These COFs are crystalline, permanently porous, and stable in boiling water, acid (9 N HCl), and base (3 N NaOH). The. synthesized COFs (all eight) were successfully delaminated using a simple, safe, and environmentally friendly mechanical grinding route to transform into covalent organic nanosheets (CONs) and were well characterized via transmission electron microscopy and atomic force microscopy. Further PXRD and FT-IR analyses confirm that these CONs retain their structural integrity throughout the delamination process and also remain stable in aqueous, acidic, and basic media like the parent COFs. These exfoliated CONs have graphene-like layered morphology (delaminated layers), unlike the COFs from which they were synthesized.

Mechanochemical synthesis of chemically stable isoreticular covalent organic frameworks - Biswal, Bishnu P.; Chandra, Suman; Kandambeth, Sharath; Lukose, Binit; Heine, Thomas; Banerjeet, Rahul (Journal of the American Chemical Society, 2013)
Three thermally and chemically stable isoreticular covalent organic frameworks (COFs) were synthesized via room-temperature solvent-free mechanochemical grinding. These COFs were successfully compared with their solvothermally synthesized counterparts in all aspects. These solvent-free mechanochemically synthesized COFs have moderate crystallinity with remarkable stability in boiling water, acid (9 N HCl), and base [TpBD (MC) in 3 N NaOH and TpPa-2 (MC) in 9 N NaOH]. Exfoliation of COF layers was simultaneously observed with COF formation during mechanochemical synthesis. The structures thus obtained seemed to have a graphene-like layered morphology (exfoliated layers), unlike the parent COFs synthesized solvothermally.

Phosphoric acid loaded azo (-N=N-) based covalent organic framework for proton conduction - Chandra, Suman; Kundu, Tanay; Kandambeth, Sharath; BabaRao, Ravichandar; Marathe, Yogesh N.; Kunjir, Shrikant M.; Banerjee, Rahul (Journal of the American Chemical Society, 2014)
Two new chemically stable functional crystalline covalent organic frameworkds (COFs) (Tp-Azo and Tp-Stb) were synthesized using the Schiff base reaction between triformylphloroglucinol (Tp) and 4,4'-azodianiline (Azo) or 4,4'-diaminostilbene (Stb), respectively. Both COFs show the expected keto-enamine form, and high stability toward boiling water, strong acidic, and basic media. H3PO4 doping in Tp-Azo leads to immobilization of the acid within the porous framework, which facilitates proton conduction in both the hydrous (sigma = 9.9 X 10(-4) S cm(-1)) and anhydrous state (sigma = 6.7 X 10(-5) S cm-1). This report constitutes the first emergence of COFs as proton conducting materials.

Role of hydrogen bonding in pseudocapacitance of covalent organic frameworks - Chandra, Suman; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: COF; H-bonding; pseudocapacitance

Construction and structural diversity of Cd-MOFs with pyrazole based flexible ligands and positional isomer of naphthalenedisulfonate - Singh, Udai P.; Singh, Neetu; Chandra, Suman (Inorganic Chemistry Communications, 2015)
In the present communication, we have reported the construction of a series of Cd(II)-MOFs using conformationally flexible ligand (CFL); 3,3',5,5'-tetramethy1-4,4'-bipyrazolyl (H(2)BPz), flexible bent ligand (FBL); methylenebis-(3,5-dimethylpyrazole) (H(2)MBPz) and positional isomer of naphthalene disulfonic acid salt ligands (1,5-NDS, 2,6-NDS). By using these ligands, four new coordination polymers namely [Cd(H(2)MBPz)(2) center dot 1,5-NDSA](n) (NDS-MOF-1), [Cd(H(2)BPz)center dot 1,5-NDSA](n) (NDS-MOF-2), {[Cd(H(2)MBPz)(2)](2+)center dot 2,6-NDSA(2-)}(n), (NDS-MOF-3) and {[Cd(H(2)BPz)(2)](2+).2,6-NDSA(n)(2-}) (NDS-MOF-4) have been synthesized. The crystal structure analysis revealed that the employment of positional isomeric naphthalene disulfonic acid salts resulted in different architectures ranging from one dimensional chain to two dimensional grid network and further connected into a three dimensional supramolecular structure through intermolecular hydrogen bonds, pi center dot center dot center dot pi and C-H center dot center dot center dot pi interactions. In addition, the photophysical properties and thermal stability studies for all the NDS-M0F5 1-4 were also investigated. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Cadmium(II); Conformation; coordination polymers; Naphthalenedisulfonate; Photophysical properties; thermal stability

Pore surface engineering in porous, chemically stable covalent organic frameworks for water adsorption - Biswal, Bishnu P.; Kandambeth, Sharath; Chandra, Suman; Shinde, Digambar Balaji; Bera, Saibal; Karak, Suvendu; Garai, Bikash; Kharul, Ulhas K.; Banerjee, Rahul (Journal of Materials Chemistry A, 2015)
Herein, we have explored the possibility of a class of covalent organic frameworks (COFs) as water adsorbing materials. We have selected, synthesized 12 chemically stable functionalized Schiff base COFs and thoroughly studied their water uptake behaviour. Further, a deep understanding was developed with these COFs towards the effects of condensation pressure of water and hydrophilic/hydrophobic groups present in the COF pores on water absorption capacity and ultimately, their recyclability. Among all reported COFs, TpPa-1 shows the highest water uptake of 30 wt% (368 cm(3) g(-1); 17 mmol g(-1)) at P/P-0 = 0.3, which is also comparable with the recently reported carbon materials and few well known MOFs. This study also reveals that the overall water uptake of COFs can be tuned systematically based on chemical functionality and pore size in a wider window of relative pressures.

Interplaying intrinsic and extrinsic proton conductivities in covalent organic frameworks - Chandra, Suman; Kundu, Tanay; Dey, Kaushik; Addicoat, Matthew A.; Heine, Thomas; Banerjee, Rahul (Chemistry of Materials, 2016)
A sulfonic-acid-based covalent organic framework (TpPa-SO3H) has been synthesized that exhibits intrinsic proton conductivity under anhydrous conditions. The sulfonic acid groups are aligned on the two-dimensional (2D) layers at periodic intervals and promote the proton hopping inside the hexagonal one-dimensional channel. The intrinsic proton conductivity of TpPa-SO3H was measured as 1.7 X 10(-5) S cm(-1) at 120 degrees C under anhydrous conditions. To enhance the proton conductivity, we have synthesized a hybrid COF TpPa(SO3H-Py) by a ligand-based solid-solution approach that contains sulfonic acid as the acidic site, as well as pyridine as the basic site, in order to immobilize acidic proton carrier molecules. Impregnation of phytic acid molecules inside the framework increases the anhydrous proton conductivity up to 5 x 10(-4) S cm(-1) at 120 degrees C. Such an approach highlights the advantage and first-time use of hybrid COF for interplaying intrinsic to extrinsic proton conductivity.

Photoactive anthraquinone-based host-guest assembly for long-lived charge separation - Jha, Ajay; Mote, Kaustubh R.; Chandra, Suman; Madhu, Perunthiruthy K.; Dasgupta, Jyotishman (Journal of Physical Chemistry C, 2021)
Porous 2D covalent organic frameworks (COF) that are assembled axially through weak p-stacking interactions can provide reticular charge transport channels while playing host to kinetically stabilized reactive molecular redox states. Here we demonstrate a host-guest supramolecular charge transfer (CT) assembly using photoactive anthraquinone-based COF as an acceptor while incarcerating the electron donor N,N-dimethylaniline (DMA) inside it. Employing femtosecond broadband transient absorption spectroscopy in combination with electron paramagnetic resonance (EPR) studies, we show that the CT occurs rapidly within <110 fs after photoexcitation, subsequently leading to long-lived charge separation with 13% quantum efficiency at room temperature. The photoinduced EPR signature of the long-lived confined DMA cation radical confirms the disparate regions of charge localization while H-1-C-13 correlation experiments using solid-state NMR spectroscopy enumerate the packing of the amines inside the host-guest COF assembly. Our work demonstrates the potency of charge transport pathways in supramolecular assemblies for efficient charge separation which if optimally tuned should pave the way for COF-based photocatalytic reaction centers.